The statistic processing of angle measurement results - Куц, Ю. В.; Щербак, Л. М. (Proceedings of National Aviation University (archive), 2021)
The probability models of the angle measurements for signals, which are described by periodic functions, have been proposed. The geometric interpretation of the angle measurement is considered. Proposed model can be used at the statistic processing of phase measurement results